Profit Increase of Microentrepreneurs through Islamic Microfinance Institution Financing Program (Case Study of BPRS Amanah Ummah) - Prasetyo, Ageng; Effendi, Jaenal; Beik, Irfan Syauqi (Department of Islamic Economics, IPB University, 2025)
The development of micro-business sector in Indonesia is one of the efforts to reduce poverty. Bank Pembiayaan Rakyat Syariah (BPRS) Amanah Ummah is an Islamic microfinance institution that enables microentrepreneurs in Bogor regency to secure capital. The funding provided by BPRS Amanah Ummah is expected to increase their business income while contributing to reduce poverty levels in Bogor regency. The aim of this research was to analyze how the distribution of Islamic microfinance from BPRS Amanah Ummah affects the profit increase of microentrepreneurs. It also analyzes the factors that affect the profit of microenterprises in Bogor. This study uses a descriptive approach combined with quantitative and qualitative approaches. The effect of the Financing Program of Islamic Microfinance Institutions (LKMS) against the profit increase of microenterprises was evaluated using the Ordinary Least Square (OLS) method. The result shows that the LKMS financing program increases profits. This is evidenced by the change in microenterprise profit after securing financing. In addition, there are several variables that can increase profits such as the duration of business, the number of employees involved, the frequency of capital received, business turnover, and level of education. The conclusion of the research is that financing provided by BPRS Amanah Ummah yields a positive and significant effect in increasing the profits of microentrepreneurs in Bogor regency.